Clinical evaluation and study on factors influencing the biliary excretion of a new oral cephem antibiotic, S-1108 - Shimizu Takeaki; Sato Osamu (CHEMOTHERAPY, 1993)
The purpose of the present study was to clinically evaluate and assess factors influencing the biliary excretion of S-1108 a now oral cephem antibiotic. The subjects were 20 surgical patients, 14 who were operated upon for cholelithiasis and 6 for other diseases who were tested for biliary excretion and gallbladder tissue concentration of S-1006, levels of bile acids in bile and examined clinically. Every patient was given oral S-1108 in a dose of 200mg. The concentrations of S-1006 in serum, gallbladder tissue and bile were measured by bioassay, and the bile acid levels in bile were determined by HPLC. These tests were performed when the patients' condition was stable. The levels of S-1006 in serum ranged from 0.02 to 1.04 μg/ml (mean 0.5±0.31μg/ml), in gallbladder bile from 0.01 to 25.1 μg/ml (mean 2.4±6. 4μg/ml), in the bile duct bile from 0.15 to 15.7μg/ml (mean 4.3±4.2μg/ml), in gallbladder tissue from0.05 to 1.98μg/ml (mean 0.5±0.5μg/ml). The levels of total bile acid in bile were 54, 784±87, 508 μ mol/L. The S-1006 levels in gallbladder tissue were very closely correlated with their concentrations in serum (r=0.76783, p<0.01), and in gallbladder bile (r=0.82923, p< 0.01), but these were not correlated with total bile acid concentration in bile. The biliary excretion of S-1108 was adequate to treat the biliary infections.The clinical efficacy of S-1108 was evaluated in 11 patients, 4 with acute cholangitis, 4 with carbuncles, 1 with wound infection, 1 with periproctal abscess and 1 with urinary tract infection. The results were excellent in 2 and good in 9 cases, respectively. 新しいエステル型経口セフェム系抗生物質S-1108の胆汁中濃度, 胆嚢組織内濃度を測定し, 本剤の胆道感染症治療における有用性について検討した。また胆道感染症を重点に11例にS-1108にて加療, その臨床効果及び副作用について観察した。胆汁中移行, 胆嚢組織内移行に関しては, 術前にS-1108を200mg経口投与し, その後平均3, 2時間後の胆嚢摘出術時に胆嚢組織, 胆嚢胆汁, 胆管胆汁, 末梢血液を採取し各々のS-1108抗菌活性物質であるS-1006濃度をBioassay法にて測定検討した。胆石症14例, 他疾患6例で, 平均年齢は65.6歳であった。S-1006の胆嚢胆汁中濃度は平均2, 4±6.4μg/ml (0.01～25.1μg/ml), 胆管胆汁中濃度は平均4-3±4.2μg/ml (0.15～15.7μg/ml), 胆嚢組織内濃度は平均0.5±0.5μg/ml (0.05～1.98μg/ml), 血清濃度は平均0.5±0.3μg/ml (0.02～1.04μg/ml) で, 良好な胆汁中, 胆嚢組織内移行を示し, 体内動態の面からは胆道感染症治療に有用な薬剤と考えられた。急性胆管炎症例4例を含む外科的感染症11例にS-1108にて加療した。投与量は11例全例が100mg×3/dayで, 投与期間は6～14, 日で, 総投与量は1.8～4.2gであった。起因菌を測定し得た9例中7例が細菌消失, 2例が減少と, その効果は優れていた。11例全例に臨床検査値の異常も含めて副作用は認められず, 効果判定では著効2例, 有効9例で, 無効例はなく, 有用な抗生物質と考えられた。